Bipolar ablation with contact force-sensing of swine ventricles shows improved acute lesion features compared to sequential unipolar ablation - Soucek, Filip; Caluori, Guido; Lehar, Frantisek; Jez, Jiri; Pesl, Martin; Wolf, Jiri; Wojtaszczyk, Adam; Belaskova, Silvie; Starek, Zdenek (Journal of cardiovascular electrophysiology, 2020)
INTRODUCTION: Despite technical progress, ventricular tachycardia (VT) recurrence after unipolar ablation remains relatively high (12%-47%). Bipolar ablation has been proposed as an appealing solution that may overcome limitations associated with unipolar ablation settings. We designed an animal study to compare bipolar (BPA) vs sequential unipolar ablation (UPA) using contact force-sensing technology on both ablation catheters. METHODS: Twenty large white female pigs (6-months-old, 50-60 kg) underwent multiple RF ablations (30 W, 60 seconds, 30 mL/min irrigation) on the ventricular myocardium from the epicardial and endocardial sides. The hearts were fixed and scanned with high-resolution cardiac magnetic resonance imaging. Thermal lesions were located and characterized in volume, depth, width, and transmurality. RESULTS: Lesion volume was calculated as the sum of epicardial or endocardial conjoined/isolated lesions at one location. Linear dimensions (width and depth) were measured twice for each location, on the endocardial and epicardial side. We evaluated 35 lesions across the intraventricular septum (UPA, N = 17 vs BPA, N = 18). No difference in volume, linear dimensions or impedance drop was observed in this area between UPA and BPA. However, BPA required half RF time and showed an increased transmurality trend. We then analyzed 73 lesions from the endocardial side (UPA, N = 35 vs BPA, N = 38) and 50 from the epicardial side (UPA, N = 11 vs BPA N = 39) of the ventricular free walls. Lesion transmurality was markedly improved by BPA (P = .030, odds ratio, 23.73 [4.71,31.96]). Ventricular BPA lesions were significantly deeper on the epicardial side (P < .0001) and endocardial side (P = .015). CONCLUSION: Bipolar ablation is more likely to create transmural and epicardial lesions in the ventricle wall. Half the time is needed for the creation of comparably deep and large lesions.
Keywords: Magnetic Resonance Imaging; magnetická rezonanční tomografie; contact force bipolar ablation; srdeční katétry; Sus scrofa; Equipment Design; Female; zvířata; katetrizační ablace; ventricular tachycardia; ženské pohlaví; design vybavení; Heart Ventricles; radiofrequency catheter ablation; myokard; thermal lesion size; Cardiac Catheters; Animals; Myocardium; Catheter Ablation; Transducers, Pressure; srdeční komory; měniče tlakové